Perancangan Value Stream Mapping untuk Mengidentifikasi dan Mengurangi Waste Pada Proses Produksi Tangki Medikal di PT. Intidaya Dinamika Sejati - Kezia Phoebe Sutanto; Prayonne Adi (Jurnal Titra, 2022)
PT. Intidaya Dinamika Sejati is a company engaged in the distribution of pedrogals, roots blowers, becker vacuum pumps, as well as technical consultants for service services for various products, such as vacuum pumps, roots blowers, air end compressors, control panels, and air locks for all brands. There are five divisions in PT. Intidaya Dinamika Blower division, Vacuum division, Fabrication division, Rewinding division, and Industrial Repair division. Fabrication Division is one of the largest divisions in PT. The Power of True Dynamics. In Fabrication division there are several wastes that can reduce the productivity of making medical vacuum pump. The wastes that exist in PT. Intidaya Dinamika Sejati Fabrication division: motion, waiting, transportation, defect, and extra processing. Researchers designed value stream mapping as a reference for improving the medical vacuum pump production process. The suggestions made for process improvement, briefing, stricter supervision and assessment, worker training, setting the hand stacker before the welding process, use of measuring tape, use of phosphating liquid to wash tanks, the uses of spray putty, and change the order of processes. Finally, the researcher made a future value stream mapping to describe the situation after the proposal.